LES DIVERSES FORMES DE DETERMINATION DANS LES LIENS DE PARENTE CHEZ LES EWE DU TOGO ET DU GHANA (A TRAVERS LES ANTHROPONYMES - Komla Enyuiamedi Agbessime (European Scientific Journal, ESJ, 2014)
This survey clarifies the various means of which the Ewes have at their disposal in the identification or in the recognition of a person in a given family through the study of his/her name. The research took in account the use of the Ewe (language spoken in the south of Togo and Ghana) in the different processes of determination in the family set up relations by the fact to name a child from the name of his/her father, his/her mother or the name of a family member. The survey raised all the different processes that intervene in this determination through the studies of a person’s name. It is about the determination on the basis of an agent complement introduced by a connector, the determination on basis of the apposition to the commutation and finally the types of determination based on economic ground.